Optimization of thermoelectric properties on Bi2Te3 thin films deposited by thermal co-evaporation - Gonçalves, L. M. (2010)
The authors thank the D.M. Rowe and Gao Min (University of Cardiff) for guidelines; Stefano Chiussi (University of Vigo, Spain) for XPS analysis, Dieter Platzek (Panco GmbH, Germany) for Seebeck image map and David Barber (University of Essex) for English amendments. We are also indebted to the Chemistry and Physics departments from University of Aveiro where the Raman scattering experiments were performed and Instituto Tecnológico e Nuclear for RBS/PIXE analysis.